The role of CyaY in iron sulfur cluster assembly on the E. coli IscU scaffold protein. - Clara Iannuzzi; Salvatore Adinolfi; Barry D Howes; Ricardo Garcia-Serres; Martin Clémancey; Jean-Marc Latour; Giulietta Smulevich; Annalisa Pastore (PLoS ONE)
Progress in understanding the mechanism underlying the enzymatic formation of iron-sulfur clusters is difficult since it involves a complex reaction and a multi-component system. By exploiting different spectroscopies, we characterize the effect on the enzymatic kinetics of cluster formation of CyaY, the bacterial ortholog of frataxin, on cluster formation on the scaffold protein IscU. Frataxin/CyaY is a highly conserved protein implicated in an incurable ataxia in humans. Previous studies had suggested a role of CyaY as an inhibitor of iron sulfur cluster formation. Similar studies on the eukaryotic proteins have however suggested for frataxin a role as an activator. Our studies independently confirm that CyaY slows down the reaction and shed new light onto the mechanism by which CyaY works. We observe that the presence of CyaY does not alter the relative ratio between [2Fe2S](2+) and [4Fe4S](2+) but directly affects enzymatic activity.